Robusta Coffee Growth Response to Application of Various Liquid Organic Fertilizers in Replacing C-Organic and N-Total Soil - Siti Mutmainah (Agrifarm : Jurnal Ilmu Pertanian, 2020)
The Ministry of Agriculture through the Agricultural Quarantine Agency (2019) stated that Robusta coffee has contributed 41% of the country's foreign exchange, with an average export frequency of 102 times per month, and will continue to increase. In connection with the growth in export volume of robusta coffee, coffee farmers need additional substances for the soil in the form of nutrients to be able to meet the soil nutrient needs for coffee from planting to harvest. Organic fertilizer in liquid form is one type of fertilizer that can be an option, in addition to facilitating nutrient absorption. This study aims to determine the response of various liquid organic fertilizers at certain concentrations to the vegetative growth of robusta coffee. The content of C-organic and total Nitogen in the soil which has been given the addition of gamal liquid organic fertilizer and tofu wastewater with the addition of citronella can provide a very significant difference in the vegetative growth of robusta coffee plants at the age of 60 HSP at plant height, and 90 HSP in diameter. stem and number of leaves (strands). Based on the results of laboratory tests carried out, it was also known that the macro and micro nutrient content in the soil with the addition of poc of tofu wastewater which was given citronella had a good content compared to the control and soil conditions with the addition of gamal liquid organic fertilizer.